2003
DOI: 10.4049/jimmunol.170.2.795
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin/Lipopolysaccharide Activates NF-κB and Enhances Tumor Cell Adhesion and Invasion Through a β1 Integrin-Dependent Mechanism

Abstract: β1 integrins play a crucial role in supporting tumor cell attachment to and invasion into the extracellular matrix. Endotoxin/LPS introduced by surgery has been shown to enhance tumor metastasis in a murine model. Here we show the direct effect of LPS on tumor cell adhesion and invasion in extracellular matrix proteins through a β1 integrin-dependent pathway. The human colorectal tumor cell lines SW480 and SW620 constitutively expressed high levels of the β1 subunit, whereas various low levels of α1, α2, α4, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 60 publications
3
102
2
2
Order By: Relevance
“…Previously, it was shown that bacterial LPS can increase colorectal carcinoma adhesion to, and subsequent invasion of cultured endothelial monolayers. 52 Thus, we assessed the influence of systemic inflammation on the early events in metastatic progression of lung carcinoma cells in vivo, and found that LPS-mediated systemic inflammation significantly increased the adhesion of H-59 cells within the liver sinusoids. These findings provide in vivo evidence that inflammation can increase the metastatic potential of circulating tumor cells by enhancing their ability to infiltrate the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that bacterial LPS can increase colorectal carcinoma adhesion to, and subsequent invasion of cultured endothelial monolayers. 52 Thus, we assessed the influence of systemic inflammation on the early events in metastatic progression of lung carcinoma cells in vivo, and found that LPS-mediated systemic inflammation significantly increased the adhesion of H-59 cells within the liver sinusoids. These findings provide in vivo evidence that inflammation can increase the metastatic potential of circulating tumor cells by enhancing their ability to infiltrate the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been extensively demonstrated that bacterial endotoxin (LPS), analysed in both in vitro and in vivo experimental settings, reduces apoptosis (Andrews et al, 2001;Wang et al, 2003) and increases proliferation in metastatic tumour cells (Coffey et al, 2006), the role of extracellular matrix (ECM)-degrading enzyme systems remains to be elucidated in this phenomenon.…”
mentioning
confidence: 99%
“…Another important factor that regulates cancer physiology in the TME is integrin receptor signaling of the cancer cells. [28][29][30] Fibroblasts are known to be a rich source of ECM components, such as fibronectin, which is a ligand for the integrin signaling in various cellular responses. [31] Because both collagen and fibrin are important in fibronectin fibrogen esis, [32] our results might suggest that a combination of ECM integrin signaling and ECM rigidity could affect such signaling.…”
Section: Angiogenesismentioning
confidence: 99%